ISU-ISU TERKINI DALAM SISTEM INFORMASI MANAJEMEN - Ali Murtadho, Muhammad; Annur, Saipul; Rosad, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines current issues in Management Information Systems (MIS) in the digital era, focusing on the role of advanced technologies such as Big Data, Cloud Computing, and Artificial Intelligence (AI). The research aims to analyze the transformation of MIS from an administrative tool into a strategic system that supports data-driven decision-making. This study employs a qualitative approach with a library research method by analyzing various relevant scientific literature. The findings indicate that the integration of Big Data, Cloud Computing, and AI significantly enhances the effectiveness, efficiency, and flexibility of MIS in organizations. However, this development also introduces several challenges, particularly in terms of information security, ethical use of data, and system integration. Issues such as cyber threats, data privacy violations, algorithmic bias, and lack of transparency become critical concerns. Additionally, organizational readiness, human resource competence, and regulatory frameworks play essential roles in successful implementation. In conclusion, while digital technologies provide substantial opportunities for improving organizational performance, their implementation must be supported by strong security systems, ethical data governance, and adequate organizational readiness to ensure sustainable and responsible use of MIS.